Toward Universal Photodynamic Coatings for Infection Control - Ghareeb, C. Roland; Peddinti, Bharadwaja S. T.; Kisthardt, Samantha C.; Scholle, Frank; Spontak, Richard J.; Ghiladi, Reza A. (Frontiers in Medicine, 2021)
The dual threats posed by the COVID-19 pandemic and hospital-acquired infections (HAIs) have emphasized the urgent need for self-disinfecting materials for infection control. Despite their highly potent antimicrobial activity, the adoption of photoactive materials to reduce infection transmission in hospitals and related healthcare facilities has been severely hampered by the lack of scalable and cost-effective manufacturing, in which case high-volume production methods for fabricating aPDI-based materials are needed. To address this issue here, we examined the antimicrobial efficacy of a simple bicomponent spray coating composed of the commercially-available UV-cross-linkable polymer N-methyl-4(4’-formyl-styryl)pyridinium methosulfate acetal poly(vinyl alcohol) (SbQ-PVA) and one of three aPDI photosensitizers (PS): ZnTMPyP4+, methylene blue (MB), and Rose Bengal (RB). Termed SbQ-PVA/PS, we applied these photodynamic coatings to a variety of commercially available materials. Scanning electron microscopy (SEM) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) confirmed the successful application of the coatings, while inductively coupled plasma-optical emission spectroscopy (ICP-OES) revealed a photosensitizer loading of 0.09-0.78 nmol PS/mg material. The antimicrobial efficacy of the coated materials was evaluated against methicillin-susceptible Staphylococcus aureus ATCC-29213 and human coronavirus strain HCoV-229E. Upon illumination with visible light (60 min, 400-700 nm, 65±5 mW/cm2), the coated materials inactivated S. aureus by 97-99.999% and HCoV-229E by 92-99.999%, depending on the material and PS employed. Photobleaching studies employing HCoV-229E demonstrated detection limit inactivation (99.999%) even after exposure for four weeks to indoor ambient room lighting. Taken together, these results demonstrate the potential for photodynamic SbQ-PVA/PS coatings to be universally applied to a wide range of materials for effectively reducing pathogen transmission.